PREPARATION AND EVALUATION OF NATURAL LIPSTICKSFROM BIXA ORELLANA SEEDS. - SWATI DESHMUKH,; MANISHA CHAVAN,; MANISHA SUTAR,; SONIA SINGH, (International Journal of Pharma and Bio Sciences, 2013)
Cosmetics are incredible in demand since historical time till day. Lipstick formulations are most widely used to enhance the beauty of lips and add glamour to touch to the makeup. With this aim and objectives, an attempt was made to formulate natural lipsticks by using colouring pigments of Bixa orellana seeds, and the lipsticks were evaluated for their organolaptic properties such as spreading, hardness, shine and gloss and found to be a satisfactory product to give attractive beauty. The preparation of these lipsticks with the natural ingredients like Bixa seeds, Olive oil, ripe fruit powder of Shikakai. Due to various adverse effects of available synthetic preparation ,the present work was conceived by us to formulate a herbal lipsticks having minimal or no side effects which will extensively used by the women of our communities with great surety and satisfaction.